Introducing an agricultural app to rice farmers: A pilot study in Can Tho, Vietnam - Bui, T.; Trinh, T.T.; Kawarazuka, Nozomi; Schepler-Luu, V. (International Potato Center, 2023)
Plantix is an agricultural app developed by a private company based in Germany which offers a diagnosis and advice for more than 30 crops. It has great potential as a new form of extension service complementing a traditional face-to-face extension service. The CGIAR Plant Health Initiative seeks to introduce the app as part of a package of innovations available for integrated pest and disease management to facilitate behavioral change among farmers. Plantix has been widely used in India but has not yet become very common in Vietnam. The aim of this pilot study was to test the usability of Plantix app for progressive rural rice growers in Vinh Thanh District, Can Tho City, Vietnam. A group of 15 farmers (5 woman and 11 men) participated in the training on use of the app and provided feedback after a two-week trial. The results show that the farmers seem to have some trust issues with the app’s diagnosis, as it reportedly failed to identify or distinguish early signs of certain pests and diseases on young rice. Nevertheless, the farmers showed interest in using Plantix app and considered it a useful tool once its early detection capacity is improved. The participants were experienced large-scaled rice farmers who were already quite familiar with the symptoms of regular pests and diseases. They agreed with the knowledge provided by Plantix. The farmers appeared to be conscious of the recommended dosage of chemical pesticides as written on product labels, however, the current local practice still involves overusing. This suggests that additional measures might be needed along with the introduction and dissemination of Plantix for a stronger impact on farmers’ behaviors. The app can be very useful for farmers when they start growing new crops, when there are new pests and diseases, and when they have difficulties distinguishing one disease from others with similar symptoms. Some of the farmers suggested the need for information about new generation pesticides. They also expressed the need for recommendations of specific “top-ranked” pesticide products, to help them navigate the large number of products and brands currently on the market. Considering the gender division of labor and decision-making, the results show that men are usually responsible for pest and disease management, but women are also involved in decision-making to some extent. It will be interesting to observe how women’s improved knowledge on pest and disease management obtained through Plantix will lead to change in household decisions on pesticide use. The participating farmers use various sources such as TV, Internet, extension workers, input suppliers and peer farmers as means of accessing information and exchanging knowledge. Male farmers tend to learn new agricultural technologies through social networks within their villages and the Internet more often, while the women do that through the Internet and TV. However, both groups trusted their own experience the most. Therefore, introducing the community’s key farmers to new technologies though demonstration and success stories could work as a strategy to ignite behavior change among peer farmers. In addition, communication via the Internet and TV could quickly reach a large number of farmers. Involving input suppliers and extension workers in the introduction of the Plantix app could also be helpful. While this pilot study focused on large-scaled farmers, there are smallholder farmers from poor households in some remote areas in the Mekong Delta. Their needs and knowledge may be significantly different from those of progressive farmers. Introducing the app to different types of farmers can help us understand the diverse needs and priorities of farmers in the process of digitalization.